Social capital contribution on the survival of business entities / Abdul Aziz Bagis - Bagis, Abdul Aziz (2019)
The number and role of SMEs in Indonesia is very large, therefore their existence needs to be safeguarded, while operating age get less attention. It is time for the measure of success for SMEs to use viability, which demonstrates the ability of businesses to sustain their business in a turbulent business environment (Bagis, 2018). The characteristics of long-lived companies include awareness and the ability to make companies as human communities, and keep up with the ongoing changes in the environment, be careful to make debt loans and give fresh and new ideas (De Geus, 1997). Building strategic cooperation, providing opportunities for success, and avoiding competing risks in the current turbulent era (W.C Kim and Moauborgne, 2002). Effective human relationships, effective trust, networks and norms, reveal the social capital of enterprises